First Report on Cationic Triphenylphosphonium Compounds as Mitochondriotropic H3R Ligands with Antioxidant Properties - Tobias Werner; Tito Añazco; Paula Osses-Mendoza; Alejandro Castro-Álvarez; Cristian O. Salas; Raquel Bridi; Holger Stark; Christian Espinosa-Bustos (MDPI AG, 2024)
Neurodegenerative diseases are a major public health problem due to the aging population and multifaceted pathology; therefore, the search for new therapeutic alternatives is of the utmost importance. In this sense, a series of six 1-(3-phenoxypropyl)piperidines alkyl-linked to a triphenylphosphonium cation derivative were synthesized as H3R ligands with antioxidant properties to regulate excessive mitochondrial oxidative stress and contribute to potential new therapeutic approaches for neurodegenerative diseases. Radioligand displacement studies revealed high affinity for H3R with Ki values in the low to moderate two-digit nanomolar range for all compounds. Compound 6e showed the highest affinity (Ki H3R = 14.1 nM), comparable to that of pitolisant. Antioxidative effects were evaluated as radical-scavenging properties using the ORAC assay, in which all derivatives showed low to moderate activity. On the other hand, cytotoxic effects in SH-SY5Y neuroblastoma cells were investigated using the colorimetric alamar blue assay, which revealed significant effects on cell viability with an unequivocally structure-toxicity relationship. Finally, docking and molecular simulation studies were used to determine the H3R binding form, which will allow us to further modify the compounds to establish a robust structure-activity relationship and find a lead compound with therapeutic utility in neurodegenerative diseases.